Emotion Expression and Substance Use in Newly Parenting Adolescents and Young Adults. Issue 7 (26th March 2015) - Desrosiers, Alethea; Sipsma, Heather; Divney, Anna; Magriples, Urania; Kershaw, Trace
<x xml:space="preserve">Abstract</x> Objective Deficits in emotion expression skills have been associated with alcohol and substance use, but the mechanisms through which these associations occur are not well understood. The current study investigated (a) associations between emotion expression and substance use (i.e., alcohol, cigarettes, and marijuana) in newly parenting adolescents and young adults and (b) whether symptoms of depression and stress mediate these associations in young mothers and fathers. Methods Participants recruited from obstetrics and gynecology clinics completed the Center for Epidemiological Studies‐Depression Scale, Perceived Stress Scale, Emotion Expression Scale for Children, and substance use items. Results Path analysis indicated that lower emotion expression at 6 months postpartum was significantly associated with more alcohol and marijuana use at 12 months postpartum for males but not females. Also among males, stress levels at 6 months postpartum partially mediated associations between emotion expression and alcohol and marijuana use at 12 months postpartum. Conclusions Findings suggest that poor emotion expression skills are related to more substance use in young fathers, and levels of stress may partially account for this association.